Coping Action Patterns in Trauma and Other Autobiographic Narratives in Holocaust survivors: A Mixed–Methods Study. Issue 10 (26th November 2021) - Békés, Vera; Perry, J. Christopher; Starrs, Claire J.
ABSTRACT: In a world where genocides and wars are constant reality, understanding the long-term psychological impact of massive trauma on survivors, as well as identifying ways to promote resilience among them are crucial. Research has repeatedly demonstrated Holocaust survivors' remarkable capacity to live with horrible memories and still function well; however, the exact nature of defensive and coping processes that allowed this have remained mostly unclear. The present study aims to address this question by identifying Coping Action Patterns in survivors' Holocaust (HN) versus other, pre- and post-Holocaust (ON) narratives. We analyzed 169 thematic units in 20 in-depth interviews with Holocaust survivors using a sequential explanatory mixed-method approach. We found that the proportion of adaptive coping patterns was higher in HN compared to ON, and that the coping category Relatedness, as well as specific individual coping strategies: Self-Reliance, Escape, and Information Seeking occurred more frequently in HN compared to ON, although none of these differences reached statistical significance. A modified interpretative phenomenological approach was used to identify common themes within each coping strategy. The results implicate that maintaining a dual representation of trauma versus regular, non-traumatic autobiographic memories may play a crucial role in the resilience of massive trauma survivors.